Differential Diagnosis and Management of Fatigue in Multiple Sclerosis: Considerations for the Nurse - Costello, Kathleen; Harris, Colleen (The Journal of neuroscience nursing, 2003)
Fatigue is one of the most disabling aspects of multiple sclerosis (MS), affecting an estimated 70%-90% of patients. Yet, despite its prevalence, it is also one of the most difficult MS symptoms to accurately diagnose and effectively treat. This is because of numerous factors, including the subjective and nonspecific nature of fatigue; its variable manifestations; its similarity to psychological, motor, cognitive, respiratory, and non-MS-related disturbances and conditions; and a lack of understanding of its precise etiology. In contrast to fatigue experienced by people without MS, MS fatigue is characterized by its persistence and sensitivity to core and ambient temperatures. Differential diagnosis of MS fatigue is largely dependent on delineating chronic versus acute onset and determining whether fatigue is a symptom in and of itself (primary MS fatigue) or an aspect of an MS-related or non-MS-related etiology (secondary MS fatigue). Once the presence of fatigue is established, a through medical history, physical examination, and fatigue assessments can guide effective management, which includes education, self-care strategies, and pharmacological treatment. As patient advocates and gatekeepers, MS nurses are in an optimal position to establish and evaluate fatigue as a symptom in and of itself and effectively guide this process.